Being modern in the Middle East : revolution, nationalism, colonialism, and the Arab middle class - Watenpaugh, Keith David, 1966- (Princeton University Press, 2006)
In this innovative book, Keith Watenpaugh connects the question of modernity to the formation of the Arab middle class. The book explores the rise of a middle class of liberal professionals, white-collar employees, journalists, and businessmen during the first decades of the twentieth century in the Arab Middle East and the ways its members created civil society, and new forms of politics, bodies of thought, and styles of engagement with colonialism. Discussions of the middle class have been largely absent from historical writings about the Middle East. Watenpaugh fills this lacuna by draw.